Women's Vulnerability in The Swimmers (2022): An Intersectional Feminist Analysis from an Applied Linguistics Perspective - Alya Choirunia; Misbahus Surur (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
Vulnerability is an experience that is often inherent in women's lives, especially when they are in socially unequal situations. In the context of conflict and forced migration, this vulnerability becomes even more layered and complex. The film The Swimmers (2022) presents a representation of the experiences of refugee women through the story of two sisters from Syria who face war, cross-border displacement, and various forms of discrimination. This article aims to analyze how women's vulnerability is represented in the film The Swimmers using an intersectional feminist perspective. This study uses a descriptive qualitative approach with data sources consisting of 10 main scenes selected purposefully because they show the intersection between gender, refugee status, and power relations. The data were analyzed through reading the film's dialogue and visuals by linking them to the concept of intersectionality. The results of the study show that the vulnerability of women in the film is not only portrayed as a condition of marginalization and powerlessness, but also as a space for the emergence of agency, resilience, and solidarity. The contribution of this study lies in its effort to enrich the study of intersectional feminism in film analysis, particularly in reading the representation of refugee women in a more contextual and layered manner.